Spiritual Family Trees: Finding Your Faith Community's Roots - Wendland, Barbara; Easterling, Larry W. (Rowman & Littlefield Publishers, 2001)
Wendland and Easterling show you how you can use genograms in your congregation as a tool for promoting spiritual growth, building community, and enhancing communication. Spiritual Family Trees gives congregations a powerful instrument for building more intimate spiritual communities.